2012
DOI: 10.1371/journal.pone.0042717
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Inhibits Hepatocyte Growth Factor Induced Motility and Invasion of Hepatocellular Carcinoma Cells through Early Growth Response Protein 1

Abstract: The Hepatocyte Growth Factor (HGF)/c-Met signaling pathway regulates hepatocyte proliferation, and pathway aberrations are implicated in the invasive and metastatic behaviors of hepatocellular carcinoma (HCC). In addition to c-Met, heparin acts as a co-receptor to modulate pathway activity. Recently, anti-metastatic and anti-cancer effects of heparin have been reported. However, the role of heparin in the regulation of HGF signaling remains controversial and the effects of heparin on HGF-induced biological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 61 publications
5
33
0
Order By: Relevance
“…This observation is consistent with reports that EGR1 promotes the in vivo motility and invasion of hepatocellular carcinoma cells (45). Furthermore, one mechanism by which EGR1 may aid hepatocellular carcinoma proliferation in the face of nutrient limitation may be via induction of VEGF-A.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is consistent with reports that EGR1 promotes the in vivo motility and invasion of hepatocellular carcinoma cells (45). Furthermore, one mechanism by which EGR1 may aid hepatocellular carcinoma proliferation in the face of nutrient limitation may be via induction of VEGF-A.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous studies, we showed the effects of heparin on hepatocyte growth factor induced motility and invasion in hepatocellular carcinoma (HCC) cells (Ozen et al, 2012). In order to identify the molecular mechanisms of heparin mediated biological responses, we performed a gene expression array with a HCC cell line.…”
Section: Q3mentioning
confidence: 99%
“…Germany) as described previously (Ozen et al, 2012). Briefly, 5 × 10 3 HuH-7 cells/well were plated in 16-well E-Plate and placed onto the multi-plate Real-Time Cell Analyzer located inside a tissue culture incubator.…”
Section: Immunofluorescent Analysis Of the Cellsmentioning
confidence: 99%
“…We did not nd any correlation between raised anti-Xa levels and tumor size, or number of nodes, but this could be a type 2 error. Experimental studies on hepatoma cells have shown that heparin inhibits cellular invasion [28], whereas clinical studies have described a positive e ect of LMWHs on cancer survival [29]. Considering that raised anti Xa levels were predictive for 6-week mortality and that approximately 57% of variceal bleeders with raised anti Xa levels had HCC, this might re ect the con rmed strong association between HCC and bleeding-related mortality in portal hypertensive bleeding [30,31].…”
Section: Discussionmentioning
confidence: 99%